Pengaruh Kemampuan Dosen dalam Mengelola Kelas dan Model Pembelajaran Terhadap Motivasi Belajar Mahasiswa Binus University - Benawa, Arcadius; Bali, Markus Masan; Lakonawa, Petrus (Bina Nusantara University, 2014)
The objective of the research is to study the effect of the lecturer?s ability to manage the class and the learning model on the learner?s motivation. The research was conducted in Bina Nusantara University, Jakarta from the beginning of March 2013 to May 2013 The method that is used in this research, with a sample of 150 respondents selected randomly, is path analysis method. The result of the research to shows that there is positive direct effect of (1) the lecturer?s abitity to manage the class, and (2) learning model, on the learner?s motivation.